2000
DOI: 10.1016/s0014-5793(00)01299-0
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a plant tyrosylprotein sulfotransferase: novel plant enzyme catalyzing tyrosine O‐sulfation of preprophytosulfokine variants in vitro

Abstract: An in vitro assay system to detect tyrosylprotein sulfotransferase (TPST) activity of higher plant cells was established, using synthetic oligopeptides based on the deduced amino acid sequence of a phytosulfokine-K K (PSK-K K) precursor. TPST activity was found in microsomal membrane fractions of rice, asparagus and carrot cells and it was confirmed that acidic amino acid residues adjacent to the tyrosine residues of acceptor peptides were essential to the sulfation reaction. The asparagus TPST exhibited a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 28 publications
1
37
0
1
Order By: Relevance
“…1A). The Asp residue, which was indispensable for Tyr O-sulfation of PSK (Hanai et al, 2000b), was conserved immediately N terminal to the PSK sequence. Two Arg residues (amino acids 58 and 59) and two Lys residues (amino acids 72 and 73) were found to border the PSK sequence, suggesting proteolytic processing of this precursor, as in the case of animal prohormone precursors.…”
Section: Expression Pattern Of Zepsk1mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The Asp residue, which was indispensable for Tyr O-sulfation of PSK (Hanai et al, 2000b), was conserved immediately N terminal to the PSK sequence. Two Arg residues (amino acids 58 and 59) and two Lys residues (amino acids 72 and 73) were found to border the PSK sequence, suggesting proteolytic processing of this precursor, as in the case of animal prohormone precursors.…”
Section: Expression Pattern Of Zepsk1mentioning
confidence: 99%
“…Identification of genes encoding approximately 80-amino acid precursors of PSK from various plant species revealed that each preproprotein of PSK has a secretory signal sequence at the N terminus and a PSK sequence near the C terminus flanked by dibasic amino acid residues, implying proteolytic processing similar to that of animal peptide hormones (Yang et al, 1999(Yang et al, , 2001Lorbiecke and Sauter, 2002;Igasaki et al, 2003). Tyr O-sulfation of PSK precursor, which is catalyzed by tyrosylprotein sulfotransferase in the Golgi apparatus (Hanai et al, 2000b), is essential for the biological activities of PSK . After processing and secretion, PSK binds to the Leu-rich repeat-RLK (LRR-RLK) on the plasma membranes (Matsubayashi et al, 2002).…”
mentioning
confidence: 99%
“…Although no ortholog of human TPST has been found in Arabidopsis, significant TPST activity has been detected in Golgi fractions of plant cells (14). This finding suggests that plants have evolved a plant-specific equivalent of TPST, and therefore a number of sulfated peptides are present in plants.…”
mentioning
confidence: 99%
“…Although the tyrosine sulfation motif in peptides is not clear-cut, the minimum requirement for tyrosine sulfation in plants is the presence of an aspartic acid residue N-terminally adjacent to a tyrosine residue (Asp-Tyr). Multiple acidic amino acids near this tyrosine residue significantly enhance sulfation (Hanai et al, 2000a).…”
Section: Tyrosine Sulfationmentioning
confidence: 99%